UJI PERFORMA SOUTHEASTERN ASIA-OCEANIA FLASH FLOOD GUIDANCE DALAM DETEKSI KEJADIAN BANJIR BANDANG DI INDONESIA (PERIODE TANGGAL 23 – 30 Juli 2020) - Kiki, Kiki; Faalih, Imaduddin Salma (Pusdiklat BMKG, 2020)
The Flash Flood Guidance System (FFGS) is one of the programs initiated by the World Meteorological Organization (WMO) in collaboration with several international institutions, namely the National WeatherService, Hydrologic Research Center, and USAID / OFDA, which aims to build a prediction and warning system for flash floods potential throughout the world. This project seeks to minimize the impact of flash floods which is known historically to be one of the disasters with the most destructive and deadly impacts. Indonesia is one of the countries selected to participate in the implementation of the FFGS system, and is named SAOFFG (Southeastern Asia-Oceania Flash Flood Guidance System), which was initiated in early 2016. Indonesia, to be precise BMKG, was chosen as the Regional Center for this SAOFFG project. This system has undergone an operational trial phase of 6 (six) hours from July, 23rd 2020 until now. Before operated as a daily task, a performance test must be carried out to measure the level of accuracy of the output of this system. Based on the verification results, it is known that the product accuracy level is in the good category.